Réponses

2014-01-22T23:58:13+01:00
Bonsoir,

a/ (x + 1)² = 16
(x + 1)² - 16 = 0
(x + 1)² - 4² = 0
(x + 1 - 4)(x + 1 + 4) = 0
(x - 3)(x + 5) = 0
x - 3 = 0   ou   x + 5 = 0
x = 3   ou   x = -5

b/ (x + 5)(x - 5) = 39
x² - 25 = 39
x² - 25 - 39 = 0
x² - 64 = 0
x² - 8² = 0
(x - 8)(x + 8) = 0 
x - 8 = 0   ou   x + 8 = 0
x = 8   ou   x = -8

c/ (x - 7)² = 49
(x - 7)² - 49 = 0
(x - 7)² - 7² = 0
(x - 7 + 7)(x - 7 - 7) = 0
x(x - 14) = 0
x = 0   ou   x - 14 = 0
x = 0   ou   x = 14

d/ (x + 1)² = 16/25
(x + 1)² - 16/25 = 0
(x + 1)² - (4/5)² = 0
(x + 1 - 4/5)(x + 1 + 4/5) = 0
(x + 5/5/ - 4/5)(x + 5/5 + 4/5) = 0
(x + 1/5)(x + 9/5) = 0
x + 1/5 = 0   ou   x + 9/5 = 0
x = -1/5   ou  x = -9/5